2021
DOI: 10.29359/bjhpa.13.3.05
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between participation in physical activity and healthy nutrition: An example of a sports science faculty

Abstract: Background: It is important to encourage people to participate in physical activities and to develop motivational approaches to healthy nutrition in order to maintain a healthy life. This study was conducted to examine the relationship between the physical activity levels of university students and their attitudes to healthy nutrition. Material and methods: 392 (153 female and 239 male) university students voluntarily participated in the study. In the study, the International Physical Activity Questionnaire-Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
2
1
0
Order By: Relevance
“…A study conducted among Turkish high school students found that attitudes towards healthy nutrition were at a moderate level [17]. Another study conducted among university students revealed a high level of healthy eating attitudes among students [26]. In parallel with other studies conducted among different age groups, it can be interpreted that students have a healthy eating attitude in this study [17,27].…”
Section: Discussionsupporting
confidence: 84%
“…A study conducted among Turkish high school students found that attitudes towards healthy nutrition were at a moderate level [17]. Another study conducted among university students revealed a high level of healthy eating attitudes among students [26]. In parallel with other studies conducted among different age groups, it can be interpreted that students have a healthy eating attitude in this study [17,27].…”
Section: Discussionsupporting
confidence: 84%
“…For instance, Vançelik et al (2007) discovered that university students who engaged in regular sports activities exhibited higher scores in healthy nutrition attitudes compared to their non-active peers. This trend was also observed in various studies involving university students, demonstrating that those who partook in regular physical activity generally displayed more favorable attitudes towards healthy nutrition (Arı & Çakır, 2021). Moreover, Yılmaz et al (2022) conducted a study focusing on healthy nutrition attitudes among university students and found a significant difference based on the frequency of physical activity.…”
Section: Discussionsupporting
confidence: 65%
“…Inadequate diet can lead to an increased risk of obesity [ 224 ] and the development of other disorders such as diabetes, cardiovascular diseases, or hypertension [ 225 ]. Scientific reports increasingly suggest that health-promoting behaviors such as physical activity, eating a Mediterranean-style diet, and cognitive training protect cognitive functions [ 226 , 227 , 228 ]. The Mediterranean diet is suggested to have a positive effect on cognitive functions and episodic memory and is associated with a lower risk of cognitive disorders and neurodegenerative diseases [ 38 ].…”
Section: Discussionmentioning
confidence: 99%